Applicability of the third molar maturity index for assessment of age of majority in Eastern China. (November 2019) - Wang, Miaochen; Fan, Linfeng; Shen, Shihui; Bai, Xuebing; Wang, Jian; Ji, Fang; Tao, Jiang
Highlights: I3M  < 0.08 shows the best performance for discriminating adults from minors in Eastern Chinese population. A two-by-two contingency table evaluated the performance of the cut-off value of I3M . The best specific I3M cut-off was determined based on maximum Youden index. Abstract: From a legal and penalty point of view, it is essential to conclude if an individual has reached the legal age (also known as age of majority). Although Cameriere's third molar maturity index (I3M ) has been used to discriminate between adults and minors, no study has tested the applicability of I3M in the Eastern Chinese population. The aim of this study was to assess the validity of the region-specific cut-off value of I3M for discriminating minors from adults in an Eastern Chinese population. Five hundred fifty-six subjects (276 males and 280 females) aged 14–24 years participated in this study. A logistic regression analysis was conducted by considering the adult and minor ages as dichotomous dependent variables and I3M and sex as predictor variables. The results showed that sex was not statistically significant in distinguishing adults and minors. The receiver operating curve analysis showed the best performance of the cut-off value of I3M  < 0.08 in discriminating adults from minors. Furthermore, the diagnostic test showed the proportion of accuracy was 90.22% in males and 86.43% in females. The sensitivity and specificity for males were 88% and 94.06%, respectively, while those for females were 83.71% and 91.18%, respectively. The estimated Bayes post-test probability was 97.18% and 96.01% in males and females respectively. Therefore, I3M  < 0.08 may be a useful tool for indicating the legal age in Eastern Chinese population.